2019
DOI: 10.1002/jcb.29121
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor activity of sevoflurane in HCC cell line is mediated by miR‐29a‐induced suppression of Dnmt3a

Abstract: Sevoflurane (SEVO) is widely applied as an anesthetic. More recently, its antitumor capacity has been reported. However, potent mechanisms are still incompletely ascertained. In our current study, we attempted to elucidate a potent mechanism associated with microRNA (miR)‐29a/DNA methyltransferase 3 alpha (Dnmt3a) in hepatocellular carcinoma (HCC) cells. After transfection and stimulation with SEVO, biological activities of Huh7 and HepG2 cells were evaluated using the cell counting kit‐8, Annexin V‐fluorescei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…The advanced insights into the predictive and prognostic relevance of miR-29a in HCC patients are summarized in Table 6. There are several studies reported that decreased expression levels of miR-29a act as a biomarker of HCC tissue [45,53,55,56,65,66,70,84,85]. Parpart et al have identified an inverse correlation between miR-29a and AFP where tumor miR-29a level decrease significantly as serum AFP levels increase.…”
Section: Mir-29a As a Diagnostic/prognostic Indicatormentioning
confidence: 99%
“…The advanced insights into the predictive and prognostic relevance of miR-29a in HCC patients are summarized in Table 6. There are several studies reported that decreased expression levels of miR-29a act as a biomarker of HCC tissue [45,53,55,56,65,66,70,84,85]. Parpart et al have identified an inverse correlation between miR-29a and AFP where tumor miR-29a level decrease significantly as serum AFP levels increase.…”
Section: Mir-29a As a Diagnostic/prognostic Indicatormentioning
confidence: 99%
“…Another study from Sun et al (13) showed that Sevo inhibited migration and invasion of colorectal cancer cells by regulating miR-34a. Notably, Song et al (14) found that Sevo restored the expression of miR-29 and in turn miR-29a inhibition abolished the antitumor property of Sevo in HCC cells. Nonetheless, whether Sevo exerts its antitumor effect by regulating miRNA in HCC is not fully clear.…”
Section: Introductionmentioning
confidence: 99%
“…MiR-29a inhibited the expression of recombinant claudin 1 (CLDN1) to reduce the migration and proliferation of HCC cells [9]. After the overexpression of miR-29a in HCC cells, Dnmt3a was down-regulated to mediate epigenetic regulation of methylation [10]. These results suggested that miR-29a played an important role of antitumor activity in HCC.…”
Section: Introductionmentioning
confidence: 92%